Distilling Reference Architectures from Open Source Repositories - Tran, Thi Dinh (Proceedings (IEEE/ACM International Conference on Software Engineering Companion. Online), 2025)
Reference architectures (RAs) play a crucial role in simplifying and speeding up the design and evolution of software systems across various domains. However, RAs are expensive to define due to the need to combine comprehensive design knowledge from specific application domains (e.g., e-commerce, automotive) and technical contexts (e.g., cloud systems, mobile apps, IoT). Leveraging architectural information from opensource repositories via repository mining presents a promising avenue to analyze and synthesize RA-related practices, thereby enabling the development of more domain-specific RAs. This research proposes a methodology that not only distills RAs from open-source repositories but also fosters architectural reuse.